Recycling of lithium-ion batteries: cobalt recovery with supercritical fluids - Rodolfo Morales Ibarra; Motonobu Goto; Saida Mayela García Montes; Enrique Manuel López Cuellar; Azael Martínez de la Cruz (Materials for Renewable and Sustainable Energy)
Abstract A long-term recycling strategy integrated into the circular economy of materials will be the only feasible option going forward on the use of lithium-ion batteries; the development of such a technology is critical to achieving a sustainable state of energy and waste management. Supercritical fluids are great technological candidates for recycling lithium-ion batteries and recovering cobalt which can be then integrated into a circular economy through the industrialization of an efficient recycling process. Cobalt recovery is feasible using supercritical CO2, supercritical and subcritical water with organic acids with up to 99% efficiency.